2021
DOI: 10.1111/pedi.13249
|View full text |Cite
|
Sign up to set email alerts
|

Expect the unexpected: Adolescent and pre‐teens' experience of diabetes technology self‐management

Abstract: Objective Only 17% of adolescents with type 1 diabetes (T1D) are currently meeting their glycemic targets despite advances in diabetes technologies. Self‐management behaviors and challenges specific to use of diabetes technologies are insufficiently studied in adolescents. We aimed to describe the experience of diabetes technology self‐management, including facilitators and barriers, among preteens/adolescents with low and high A1C. Research Design and Methods Youth (10‐18 years of age) with T1D who use insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is important to recognize the interaction between positive experiences for the person living with diabetes and technology success, as well as the fact that the biggest barrier to using technology to its full potential is human factors that limit the effective use thereof (Gonder-Frederick et al, 2016). The use of diabetes technology has not been sufficiently studied in the adolescent population (Faulds et al, 2021). No intervention program focusing on adjustment to closed loop technology could be found in the literature search.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…It is important to recognize the interaction between positive experiences for the person living with diabetes and technology success, as well as the fact that the biggest barrier to using technology to its full potential is human factors that limit the effective use thereof (Gonder-Frederick et al, 2016). The use of diabetes technology has not been sufficiently studied in the adolescent population (Faulds et al, 2021). No intervention program focusing on adjustment to closed loop technology could be found in the literature search.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…Many of them experience daily fear and worry about medical procedures (Castensøe‐Seidenfaden et al, 2017; Shepard et al, 2014), and report feeling different from others (Sparapani et al, 2015). Diabetes self‐care is particularly stressful for adolescents (Faulds, Grey, et al, 2021), as their accelerated growth affects glucose levels in ways that may hinder their striving for independence (Cameron et al, 2018). In adolescence, doses are frequently missed for various reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In adolescence, doses are frequently missed for various reasons. For example, there can be lack of communication between adolescents and their parents about insulin‐pump self‐management (Faulds, Karnes, et al, 2021; Lindholm Olinder et al, 2011); adolescents have reported being distracted (i.e., having other matters on their minds) and, therefore, losing focus on their treatment (Lindholm Olinder et al, 2011); and adolescents may simply forget to take the doses (Faulds, Grey, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation